Green materials for carbon storage in depleted oilfields: An experimental study. (2022) - Singh, Alpana; Chaturvedi, Krishna Raghav; Sharma, Tushar
Abstract: The incessant rise in global temperature due to the large increase in anthropogenic carbon emissions over the past century threaten to undo gains made by human civilization and it has become essential that techniques to reduce atmospheric carbon be explored. For this, carbon-negative technologies like carbon geo-storage hold high vitality for industrial applications. In carbon geo-storage, captured CO2 is injected into the subsurface formations like depleted oilfields. However, the injected CO2 tends to undergo viscous fingering, bypassing small pore throats and consequently, the volumetric storage efficiency is reduced. Thus, there is a need for new mobility control agents which not only improve the volumetric storage efficiency of CO2 but also help alter rock surface for longer CO2 retention. Thus, in this study, the use of a novel green surfactant (S) has been explored in conjunction with natural polymers (P), guar gum and xanthan gum for CO2 mobility control. The composition of the SP solution was finalized via contact angle studies in presence of CO2 . Following this, CO2 injection at varying flow rates (30–90 ml/h) was investigated in sand-packs of porosity 27–31% and permeability ≈682–812 mD which was saturated with a residual reservoir brine of 4 wt% NaCl. The role of the green SP solution was validated by injecting a slug of 0.3 pore volume (PV) before CO2 injection and the time to breakthrough for gas, the liquid return before breakthrough and the pressure drop profiles were carefully analyzed. It was found that the inclusion of green surfactant improved carbon retention by a factor of 3–4.5 (in the presence of other polymers) which was also demonstrated by an increase in areal coverage inside the sand-pack (as established from the pressure drop studies). Thus, the use of a green SP solution is proposed as a mobility control agent for carbon storage in depleted oilfields.